(untitled) (Encuentros, 2016)
This paper presents the results of a research to establish whether 68 communal leaders of the District of Santa Marta (Magdalena), had knowledge and access to telework services. The aim was to identify aspects that should be strengthened in their digital literacy process. For the study a methodology of three stages was used. The main results were to identify that 95% of the population had access to information technology infrastructure, 67.6% knew about telework but 45.6% of the population only uses search services, and only 1.5% of population has generated some revenue associated with teleworking. The main reasons for not use of telework services are unfamiliarity and disinterest, though they recognize the facilities offered by the Internet. Keywords: Telework, knowledge, usage, Internet, communal leaders